Impacted canines: Etiology, diagnosis, and orthodontic management - Ranjit Manne; ChandraSekhar Gandikota; Shubhaker Rao Juvvadi; Haranath Reddy Medapati Rama; Sampath Anche (Wolters Kluwer Medknow Publications, 2012)
Impaction of maxillary and mandibular canines is a frequently encountered clinical problem, the treatment of which usually requires an interdisciplinary approach. Surgical exposure of the impacted tooth and the complex orthodontic mechanisms that are applied to align the tooth into the arch may lead to varying amounts of damage to the supporting structures of the tooth, not to mention the long treatment duration and the financial burden to the patient. Hence, it seems worthwhile to focus on the means of early diagnosis and interception of this clinical situation. In the present article, an overview of the incidence and sequelae, as well as the surgical, periodontal, and orthodontic considerations in the management of impacted canines is presented.